2005
DOI: 10.1016/j.jpainsymman.2004.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of QTc in Patients Receiving Chronic Methadone Therapy

Abstract: Recent reports suggest that methadone may prolong the QTc interval and cause torsades de pointes. This study was conducted to evaluate the prevalence of QTc prolongation during oral methadone therapy and identify factors associated with prolongation. Patients receiving oral methadone as treatment for chronic pain or addiction were eligible for the study. One hundred four patients who were receiving > or = 20 mg methadone per day for > or = 2 weeks underwent electrocardiograms to measure QTc interval duration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 16 publications
4
68
1
Order By: Relevance
“…8 Our findings are inconsistent with data in adults, in whom methadone has been associated with varying degrees of QTc prolongation (16%-23% change in QTc interval), and with torsades de pointes in up to 4% of patients. [14][15][16][21][22][23][24][25][26] Further, methadone dose, presence of interacting or other QTc-prolonging drugs, electrolyte abnormalities, and underlying cardiovascular disease have been identified as risk factors for QTc prolongation in adults, but we did not identify these associations in our population. [14][15][16][21][22][23][24][25][26] The observed differences in methadone-associated QTc prolongation may be due to physiologic differences between children and adults.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…8 Our findings are inconsistent with data in adults, in whom methadone has been associated with varying degrees of QTc prolongation (16%-23% change in QTc interval), and with torsades de pointes in up to 4% of patients. [14][15][16][21][22][23][24][25][26] Further, methadone dose, presence of interacting or other QTc-prolonging drugs, electrolyte abnormalities, and underlying cardiovascular disease have been identified as risk factors for QTc prolongation in adults, but we did not identify these associations in our population. [14][15][16][21][22][23][24][25][26] The observed differences in methadone-associated QTc prolongation may be due to physiologic differences between children and adults.…”
Section: Discussionmentioning
confidence: 81%
“…11 Furthermore, critically ill children are likely to receive other QTc-prolonging drugs, have electrolyte derangements, and have end-organ dysfunction known to be associated with increased risk for QTc prolongation. [12][13][14][15][16][17] Because methadone administration is prevalent in pediatric intensive care units, we must ensure that existing clinical practice of methadone administration does not cause undue, life-threatening harm. Therefore, we aimed to determine the effects of methadone initiation on QTc interval in critically ill children, including those with underlying cardiac disease.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with non-malignant pain, minor increases and fluctuations in QTc during a prolonged treatment with methadone in doses of less than 100 mg/day were found [5]. In a mixed population of patients with chronic pain or maintenance therapy receiving methadone with median doses of 110 mg/day, 33 % of patients had QTc prolongation related to methadone dose, but no patient had a QTc longer than 500 ms [2].…”
Section: Discussionmentioning
confidence: 98%
“…In another study, female sex, medications interfering, hypomagnesemia, structural cardiac disorder and hypokalemia were considered as the risk factors for QTc prolongation and TdP (24). Cruciani et al (25) showed that 33% had QTc prolongation (males 40%, females 20%; P = 0.03) and a marked dose response was obtained in males on methadone < 12 months (r = 0.60, P = 0.02). They also suggested that methadone may prolong the QTc interval in specific subpopulations but it poses little risk of serious prolongation.…”
Section: Discussionmentioning
confidence: 98%